Application of volatile adsorption process to tire component stock preparation technology employing air-steam bed conveyor transport - Syritsyn, Leonid; Vlasov, Genadij; Tchemerinski, Viatcheslav (Journal of Environmental Engineering and Landscape Management, 2005)
The paper describes technical and environmental aspects of hardware implementation of air‐steam bed conveyor system aimed at creating a pollution‐free zone at the stock preparation department of a tire factory. The approach presented will facilitate volatile compound adsorption into the air‐steam space from an adhesive film formed by assembling solution on the tread surface. A model of saturated adsorbent desorption, with electric contact heat applied, is developed. The results of mathematical modeling of assembling solution‐volatile matter adsorption are presented. Article in Russian. Techniniai lakiųjų organinių junginių absorbavimo padangų detalių gamybos metu transportiniuose įrenginiuose su oro garų tarpsluoksniais sprendimai Santrauka. Išanalizuoti padangų detalių gamybos transportiniuose įrenginiuose su oro garu tarpsluoksniais techniniai ir ekologiniai aspektai. Klijavimo metu išsiskyrę lakieji organiniai junginiai adsorbuojami į oro garų tarpsluoksnį. Straipsnyje pateikta adsorbento, prisotinto naudojant elektrokontaktinę šilumą, schema. Pateikti matematinio modeliavimo rezultatai leidžia geriau įvertinti lakiųjų organinių junginių adsorbcijos procesą. Reikšminiai žodžiai: klijavimas, padangų detalių gamyba, oro garų tarpsluoksnis, adsorbcijos procesas, lakieji organiniai junginiai. Аннотация. Проанализированы технические и экологические аспекты аппаратурного оформления заготовительного участка протекторных заготовок в производстве шин транспортными системами с паровоздушной несущей прослойкой для организации «чистой зоны». Подобное техническое решение способно реализовать процесс адсорбции легколетучих соединений из клеевой пленки протектора в область паровоздушной среды несущей прослойки. Рассмотрена схема десорбции насыщенного адсорбента при электроконтактном способе подвода тепла. Представлены результаты математического моделирования процесса адсорбции легколетучих соединений клеевой композиции. Ключевые слова: клеевая композиция, протекторное полотно, клеевая пленка, паровоздушная несущая прослойка, процесс адсорбции, легколетучие соединения. First Published Online: 14 Oct 2010